The impact of nutritional status on the incidence of back pain in school-aged children - a study using the Cole’s index - Zieliński, Grzegorz; Filipiak, Zuzanna; Suwała, Marta; Kozłowska, Aleksandra; Ginszt, Michał (Journal of Education, Health and Sport, 2018)
Introduction: Disorders of nutritional status have a significant impact on the dysfunction of many body systems. Emerging evidence suggests that abnormal nutritional status has a significant impact on the occurrence of bone degeneration, joint damage and it leads to an increased occurrence of back pain. According to WHO, 36% of boys and 23% of girls among Polish teenagers are overweight. In contrast, protein-energy malnutrition may affect up to 13% of children. The aim of the study: Anthropometric assessment of nutritional status and its impact on the frequency of back pain in school-age children. Methods and materials: 241 people applied for the study (female = 141, male = 100) aged 10 to 17 years (average age=14 years ± 3 years). The examined people did not suffer from any chronic diseases, they were in general good health. Interviews have focused on the occurrence of back pain in the last 3 months and at the time of the study. During the physical examination, anthropometric measurements (body weight and height) were made. On their basis, the BMIs were calculated, which were compared to the 50th percentile (OLA, OLAF centiles) giving the Cole index. The Shapiro-Wilk tests, t-Student test, and U Mann - Whitney tests were used for statistical calculations. Results: The incidence of pain in the presence of abnormal nutritional status is by 15.38 percentage points higher than in examined persons without abnormal nutritional status. However, the frequency of the absence of pain is by 8.94 percentage points lower in people with normal body mass. Nevertheless, no statistically significant differences were observed at the significance level of 0.05. Conclusions: Based on statistical research, it seems that the abnormal nutritional status in school-aged children does not affect the increased incidence of back pain in this period. To confirm this observation, further research into a larger and more homogeneous group of subjects is recommended.